Length–Weight Relationship of Lambak Fish (Labiobarbus ocellatus) from Fishermen's Catches in the Batanghari River - Lauura Hermala Yunita; Yoppie Wulanda; Septy Heltria; Rizky Janatul Magwa; Ester Restiana Endang Gelis; M. Hariski (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Lambak fish (Labiobarbus ocellatus) is a freshwater species of ecological and economic importance in the Batanghari River. Basic biological information, particularly the length–weight relationship, is needed to understand growth characteristics and support sustainable fisheries management. This study aimed to analyze the size distribution and length–weight relationship of lambak fish based on fishermen's catches. Sampling was conducted in August 2025 through direct surveys of daily catches using traditional fishing gears. The length–weight relationship was analyzed using the equation W = aLᵇ. The results showed that the samples consisted of 22 females and 33 males. The total length of females ranged from 117–160 mm and males from 100–157 mm, with weight ranges of 15–36 g and 13–40 g, respectively. The regression coefficient (b) values of 2.1483 for females and 2.2459 for males indicated a negative allometric growth pattern. The coefficients of determination (R²) of 0.6904 for females and 0.501 for males suggested relatively strong to moderate length–weight relationships. This growth pattern reflects the species' biological response to environmental conditions